Effects of Welding Current and Material Thickness on Hardness and Tensile Strength of SPCC Steel Welded Using the Metal Inert Gas (MIG) Process - Sutrisno Sutrisno; Yohanes Maria Astomo Dwi S; Aditya Nugraha; Adhi Setya Hutama; Rudi Kristianto; Yohanes Oscar Andrian (Mechanical Engineering Department - Semarang State Polytechnic, 2026)
This study investigates the effect of welding current and material thickness on the hardness and tensile strength of cold-rolled SPCC steel welded using the Metal Inert Gas (MIG) process. Welding current was varied at 80 A, 90 A, and 100 A, while material thicknesses of 0.9 mm, 1.4 mm, and 2.0 mm were used. Specimens were prepared according to the ASTM E8 standard for tensile testing. Hardness measurements were conducted in the heat-affected zone (HAZ) and base metal using the Leeb hardness method, while tensile properties were evaluated through tensile testing. The results show that welding current and material thickness significantly affect the mechanical properties of the welded joints. The highest hardness value of 672 HLD was obtained at a welding current of 100 A with a plate thickness of 0.9 mm, whereas the lowest hardness value of 232 HLD occurred at 80 A with a thickness of 2.0 mm. The highest average tensile strength of 340.56 N/mm² was achieved at 90 A with a thickness of 1.4 mm. The results indicate that a moderate welding current provides optimal tensile performance, whereas higher current levels increase hardness due to greater heat input during the welding process. Therefore, appropriate parameter selection is essential to achieve optimal welding performance in thin SPCC steel plates.